Once bitten: New evidence on the link between IMF conditionality and IMF stigma - Irina Andone; Beatrice Scheubel (European Central Bank (ECB), 2019)
While the consequences and effectiveness of IMF conditionality have long been the focus of research, the possible negative impact of IMF conditionality on countries' willingness to ask for an IMF programme - often termed "IMF stigma" - has recently received attention particularly from policy circles. In this paper we investigate how countries' past experience with the IMF and their peers' experience with the IMF affect their likelihood of entering a subsequent IMF arrangement. Our results indicate that, even when controlling for the success of past programmes, a country is less likely to approach the IMF for help if in the past it experienced an above-average number of disbursement-relevant conditions. We find hardly any impact of peers' experience, except for Asian countries.
Keywords: F33; F53; F55; H87; 330; Financial arrangements; reserves; IMF MONA; crisis resolution